Knowledge, policy and practice in education and the struggle for social justice : essays inspired by the work of Geoff Whitty - Brown, Andrew; Wisby, Emma (UCL Press, 2020)
The essays in this volume - written by some of the most influential authors in the sociology of education and critical policy studies - take the work of educator and sociologist Geoff Whitty as the starting point from which to examine key contemporary issues in education and the challenges to social justice that they present.